Adaptive Fiber Ring Laser Based on Tapered Polarization Maintaining Fiber in Sagnac Loop for Temperature and Salinity Sensing - Yuhui Liu; Weihao Lin; Fang Zhao; Jie Hu; Jinna Chen; Huanhuan Liu; Perry Ping Shum; Xuming Zhang; Li-Yang Shao (Photonics, 2023)
An optical fiber ring laser (FRL) cavity-based sensitive temperature and salinity sensor is proposed and experimentally demonstrated. The sensor consists of a Sagnac loop with a waist of 15 µm and a total length of 30 cm made of tapered polarization-maintaining fiber (PMF). Sagnac loop dual parameter sensing was theoretically modeled and presented. The salinity sensitivity of 0.173 nm/‰ was made possible by the efficient interaction between the tapered PMF cladding mode and the external refractive index. In addition, temperature sensitivity of 0.306 nm/°C was achieved through ultrahigh birefringence of PMF. Apart from that, the previous sensing system used a broadband light source (BBS) as the input light, resulting in a wide bandwidth and a poor signal-to-noise ratio (SNR). The Sagnac loop integrated into the FRL system can achieve a high SNR of approximately 50 dB and a narrow bandwidth of 0.15 nm while serving as the filter and sensor head. Additionally, the developed sensor has the advantages of simple design, low cost, and easy fabrication. It can also extend sensing distance indefinitely within a given range, which is anticipated to have positive effects on the testing of marine environments in laboratories.